It's a man's world: Exploring women's aspirations for income opportunities in Indonesian oil palm villages - Charlotte Reich; Annkathrin Wahbi; Selina Bruns; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2025)
The expansion of male-dominated cash crops marginalizes women in the economic value chain. This issue is notably prevalent in Indonesia's continuously growing oil palm industry. Yet, there has been limited research on potential pathways for women's economic integration. This study addresses this gap by utilizing primary data collected through qualitative interviews from Jambi, a key region for oil palm cultivation. We undertake an in-depth exploration of women's work aspirations in general and specifically in relation to beekeeping, as beekeeping presents itself as a sustainable economic activity. The aim of our study is to understand how income opportunities for women in rural, agri-monoculture-dominated areas can be sustainably enhanced. The findings suggest that even though overall household income increase over the past decades due to palm oil cultivation, women nevertheless want to work. They state a variety of aspired professions which we cluster into "Traders", "Socials", and "Miscellaneous". The majority of women are open to beekeeping activities and those who are not raise concerns that could easily be addressed through information, training, and by keeping stingless bees. Our results provide insights into the socio-economic dynamics of oil palm expansion. We offer recommendations for policymakers and researchers aiming for more resilient and sustainable smallholder driven oil palm systems.
Keywords: 330